Relaxin-2 during pregnancy according to glycemia, continence status, and pelvic floor muscle function - Prudencio, Caroline Baldini [UNESP]; Nunes, Sthefanie Kenickel [UNESP]; Pinheiro, Fabiane Affonso [UNESP]; Filho, Carlos Isaias Sartorão [UNESP]; Antônio, Flávia Ignácio; de Aquino Nava, Guilherme Thomaz [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Calderon, I. M.P.; Souza, F. P.; Berghmans, B.; de Bie, R.; et al. (Springer Nature, 2022)
Introduction and hypothesis: To investigate relaxin-2 concentration comparing gestational diabetes mellitus (GDM) and non-GDM patients during pregnancy according to urinary incontinence (UI) and pelvic function status. Methods: This is a cross-sectional study evaluating 282 pregnant women from 24 weeks of gestation. The participants were divided into two groups, non-GDM and GDM, according to American Diabetes Association’s diabetes mellitus gestational threshold. In addition, according to subanalysis, both groups were subdivided according to the presence of pregnancy-specific urinary incontinence: non-GDM continent, non-GDM incontinent, GDM continent, and GDM incontinent. All participants filled in questionnaires on clinical, obstetric, and urinary continence status (International Consultation on Incontinence Questionnaire-Short Form, ICIQ-SF, and Incontinence Severity Index, ISI), followed by pelvic floor muscle evaluation by the PERFECT scheme in which strength, endurance, and speed of contractions were evaluated. Results: Serum relaxin-2 concentrations were significantly lower in pregnant women with pregnancy-specific urinary incontinence in both non-GDM and GDM patients, but GDM showed the lowest concentration. In addition, the stratification of the groups according to pelvic floor muscle strength showed that pregnant patients with GDM and modified Oxford scale 0–2 had significantly lower levels than those who were non-GDM and GDM with Modified Oxford Scale 3–5. Relaxin-2 level was much lower in GDM incontinent pregnant women with MOS 0–2 compared to the other three groups. Conclusions: Lower relaxin-2 concentration was associated with the presence of pregnancy-specific urinary incontinence, but the combination of GDM, pregnancy-specific urinary incontinence, and lower levels of pelvic floor strength led to lower levels of relaxin-2 compared to the other three groups.
Keywords: Gestational diabetes; Obstetrics; Pelvic floor; Pregnancy; Relaxin-2